Language Planning and Monolingual Dictionaries: With Special Reference to Ndebele - Hadebe, Samukele (Lexikos, 2007)
Abstract: The first monolingual Ndebele dictionary, Isichazamazwi SesiNdebele, had a number of effects on Ndebele, some of which with implications for language planning. One such language planning activity was the standardization of Ndebele. The article focuses on the standardization of vocabulary and spelling. Lexicographers and most of those interested in lexicographic issues are familiar with the challenges posed by what constitutes the standard vocabulary or the standard meaning of words. These questions were crucial for a general monolingual dictionary like Isicha-zamazwi SesiNdebele. General dictionaries are the standard dictionaries for particular languages, assumed to be reflective of the ’standard usage’ of that given language in terms not only of spelling but also of meaning.The Ndebele dictionary is based on a corpus which means that words perceived by some as foreign or as ’bad’ language are considered for lemmatization. Problems were also encountered with the spelling of these loanwords. By making decisions on which words to lemmatize and how to spell loanwords, lexicographers become involved in language planning matters. The article draws from the Ndebele dictionary-making experience to discuss the role of monolingual African language dictionaries in language planning in general. Keywords: STANDARDIZATION, GENERAL MONOLINGUAL DICTIONARY, NDEBELE, LOANWORDS, LANGUAGE PLANNING, SPELLING, STANDARD, VOCABULARY, STATUS PLANNING, CORPUS PLANNING Opsomming: Taalbeplanning en eentalige woordeboeke: Met spesiale ver-wysing na Ndebele. Die eerste eentalige Ndebelewoordeboek, Isichazamazwi SesiNdebele, het ’n aantal gevolge vir Ndebele gehad, sommige waarvan met implikasies vir taalbeplanning. Een so ’n taalbeplanningsaktiwiteit was die standaardisering van Ndebele. Die artikel fokus op die stan-daardisering van woordeskat en spelling. Leksikograwe en meeste van diegene wat hulle in leksi-kografiese kwessies interesseer, is bekend met die uitdagings gestel deur wat die standaardwoor-deskat of die standaardbetekenis van woorde behels. Hierdie vrae is beslissend vir ’n algemene eentalige woordeboek soos Isichazamazwi SesiNdebele. Algemene woordeboeke is standaardwoor-deboeke vir bepaalde tale, wat aanvaar word om die "standaardgebruik" van daardie taal te weer-spieël, nie net wat die spelling nie, maar ook wat die betekenis betref. Die Ndebelewoordeboek is op ’n korpus gebaseer, wat beteken dat woorde wat deur som-mige as vreemde of as "swak" taal beskou word vir lemmatisering oorweeg word. Probleme met die spelling van hierdie leenwoorde is ook teëgekom. Deur besluite te neem oor watter woorde om te lemmatiseer en hoe om leenwoorde te spel, raak leksikograwe betrokke by taalbeplannings-aangeleenthede. Die artikel steun op ervaring verkry uit die maak van ’n Ndebelewoordeboek om die rol van eentalige Afrikataalwoordeboeke in taalbeplanning in die algemeen te bespreek. Sleutelwoorde: STANDAARDISERING, ALGEMENE EENTALIGE WOORDEBOEK, NDEBELE, LEENWOORDE, TAALBEPLANNING, SPELLING, STANDAARD, WOORDESKAT, STATUSBEPLANNING, KORPUSBEPLANNING